Thermal analysis of a 6s4p Lithium-ion battery pack cooled by cold plates based on a multi-domain modeling framework. (5th June 2020) - Zhang, Hongya; Li, Chengshuai; Zhang, Runjie; Lin, Yixin; Fang, Haisheng
Highlights: 3D thermal modeling of 6s4p Li-ion battery pack with 14 cells is performed. A multi-channel parallel cold plate is designed for the cooling of the battery pack. The cooling performance of the battery pack under different conditions is modeled. Thermal responses of Li-ion battery under external shorting are simulated. Multi-scale multi-domain modeling is demonstrated for large Li-ion battery pack. Abstract: Lithium-ion (Li-ion) batteries are the most promising power source for pure electric vehicles (EVs) and hybrid electric vehicles (HEVs) due to the batteries' high specific energy, low self-discharge rate, low weight, long lifecycle, and no memory effect. The enormous heat generation, however, limits the performance and even causes safety problems. Thermal control of the battery cells remains a challenging issue although much research has been conducted on this topic. In this study, a three-dimensional analysis of Li-ion battery cells and a 6s4p (6 serial and 4 parallel batteries in a stage) battery pack consisting of 24 prismatic batteries was performed using a multi-domain modeling framework. The well-known Newman, Tiedemann, Gu, and Kim (NTGK) model was used for subscale electrochemical modeling and the problem of heat generation due to electrical resistance, electrochemical reactions, and temperature was solved in the cell domain. The temperature evolutions at a high discharge rate and during external shorting were obtained. Strategies for modifying the cooling water states or designing cold plates with special channels to release the generated heat were proposed. It was found that although the temperature of the running battery increased quickly to 80 °C, which could trigger a thermal runaway, the cell temperature and temperature gradients were maintained at a tolerable level at a suitable coolant inlet velocity and temperature, even at a 5C discharge rate and under external shorting conditions. For a large-scale battery pack, the heat generated by the Li-ion cells accumulates inside the module, which poses a high risk of thermal runaway. The cold water flowed into the center of the battery pack through channels and the predicted maximum cell temperature and maximum temperature difference in the pack were maintained below 40 °C and 5 °C respectively at a 5C discharge rate.